The Influence of Chat GPT on EFL Students’ Descriptive Writing: A Case Study - I Gusti Agung Vony Purnama; Ida Ayu Maharani; Ni Made Dwi Ening Savitri; Ni Made Resti Widiani; Agung Rahma Suputra (RETORIKA: Jurnal Ilmu Bahasa, 2025)
The development of Artificial Intelligent (AI) has taken teachers’ attention particularly in teaching English for the EFL students. Based on the observation and interview to some students, Chat GPT is a part of AI that frequently used by the students in learning English especially in English writing skill. This study aims to investigate the influence of Chat GPT on EFL students’ descriptive writing and to find out their attitude toward the use of Chat GPT in learning English. The number of participants was twenty five from one class that enrolled English I subject. This study applied a mixed method research design which combined the quantitative and qualitative approaches. The data of this study was obtained from the pre-post-test of the students’ writing and semi-structure interview. The data of the pre-post-test writings was analyzed based on the descriptive text writing rubric. The semi-structure interview was analyzed descriptively. The finding revealed that there was an influenced on the use of Chat GPT on the students’ descriptive writing and there was also a positive attitude toward the use of Chat GPT in learning English particularly in writing task. However, they realized that they should not overly rely on this tool and still need the guidance from the teacher. It is expected that the results of this study can be used as the reference for the language teaching and learning process.